2013
DOI: 10.1186/1556-276x-8-414
|View full text |Cite
|
Sign up to set email alerts
|

The microwave-assisted ionic liquid nanocomposite synthesis: platinum nanoparticles on graphene and the application on hydrogenation of styrene

Abstract: The microwave-assisted nanocomposite synthesis of metal nanoparticles on graphene or graphite oxide was introduced in this research. With microwave assistance, the Pt nanoparticles on graphene/graphite oxide were successfully produced in the ionic liquid of 2-hydroxyethanaminium formate [HOCH2CH2NH3][HCO2]. On graphene/graphite oxide, the sizes of Pt nanoparticles were about 5 to 30 nm from transmitted electron microscopy (TEM) results. The crystalline Pt structures were examined by X-ray diffraction (XRD). Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Carbon coating CdTe nanowires are synthesized via a one-step hydrothermal process using ascorbic acid as carbonization source [14]. A synthetic route to prepare carbon-coated copper or nanoparticles is developed in an ionic liquid under microwave heating [15]. Li 3 V 2 (PO 4 ) 3 /C cathode materials can be prepared by solid-state method with sucrose as carbon source [16].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon coating CdTe nanowires are synthesized via a one-step hydrothermal process using ascorbic acid as carbonization source [14]. A synthetic route to prepare carbon-coated copper or nanoparticles is developed in an ionic liquid under microwave heating [15]. Li 3 V 2 (PO 4 ) 3 /C cathode materials can be prepared by solid-state method with sucrose as carbon source [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, catalytic applications of Pt NPs supported onto graphene are well established, which include its use as electrocatalyst for methanol oxidation reaction (Pt/graphene nanosheet surface [GNS]) [109] and for proton exchange membrane fuel cell (PEMFC) (Pt/rGO) [110], electrochemical sensors (Pt/G) [111], alcohol oxidation (Pt/rGO) [112], styrene hydrogenation (PtNPs/G) [113], etc. Aday et al [114] reported the development of highly crystalline, colloidally stable and highly monodisperse Pt NPs@rGO and its use as a catalyst for the synthesis of acridinedione derivatives which are well recognized to possess numerous biological activities such as anticancer, antimicrobial, myorelaxant, free radical scavenging, etc.…”
Section: Metal Oxide Nps Supported On Go/rgo Catalyzed Organic Transfmentioning
confidence: 99%
“…When conventional heating methods (e.g., oil bath) and other solvent were used, fewer or no nanostructures formed. Other studies also reported successful syntheses of nanostructures of Au, Pt and Rh using the MAIL technique [41,42,43,44,45,46,47,48,49,50,51]. Many researchers emphasize that ILs act as steric stabilizers, solvents and/or microwave absorbers during synthesis of metal nanostructures [41].…”
Section: Preparation Of Inorganic Nanomaterialsmentioning
confidence: 99%